A cross-sectional study on the deprivation and sex differences in health-related fitness measures in school children. Issue 1 (2nd January 2020) - Tyler, Richard; Mackintosh, Kelly A.; Spacey, Hannah L.; Stratton, Gareth
ABSTRACT: This study aimed to investigate deprivation and sex differences in selected health-relatedfitness measures in 9-12-year-old children. Data were captured on 3, 407 children (49.3% boys; aged 10.5 ± 0.6 years). Cardiorespiratory fitness(20 m multistage shuttle run test; 20 m MSRT), muscular strength (handgrip strength) and body mass index (BMI) were measured. Welsh Index of Multiple Deprivation (WIMD) scores were used to make quintile groups. A two-way Analysis of Variance examined differences in BMI z-score by sex and WIMD quintiles. Two-wayAnalysis of Covariances investigated the effect of sex and WIMD quintiles on grip strength and shuttles achieved in 20 m MSRT, adjusting for BMI z-score and maturation, repectively. Independent of sex, children in the middle quintile had a significantly higher mean BMI z-score ( p = 0.029) than their least deprived counterparts. There was a significant increase in grip strength ( p = 0.005) and20 m MSRT (boys p < 0.001; girls p = 0.028) between most and least deprived quintiles. Significant differences in 20 m MSRT score were more apparent with decreases in deprivation in boys.Overall, inequalities exist in health-related fitness by sex and deprivation. These results can be used to inform focused services to improve current and future health.